Assessment of the Impact of Early Diagnosis and Early Treatment in the Integrated Control of East Coast Fever (ECF) Involving Acquired Immunity Induced by Natural Infection in Ankole Cattle - Nanteza, Ann; Nsubuga, Julius; Kazibwe, Anne; Terundaja, Clare; Matovu, Enock; Lubega, George William (Pathogens, 2023)
The integrated control of East Coast fever (ECF) by early diagnosis and treatment involving acquired immunity induced by natural infection in Ankole cattle was assessed. A longitudinal study was carried out in Kiruhura district, southwestern Uganda for six months on 244 Ankole breed of cattle from 18 herds under natural tick challenge and relaxed tick control measures. Calves aged three to six months old were recruited and monitored daily by farmers for detection of ECF clinical symptoms. The reported sick animals were treated using Buparvaquone and treatment outcome determined. Monthly follow-ups and blood collections were done to monitor ECF status. Blood was analyzed for Theileria parva parasites by microscopy, DNA by polymerase chain reaction (PCR) and antibodies by enzyme-linked immunosorbent assay (ELISA). The overall prevalence of ECF clinical disease within six months period was 30.3% (74). The major symptoms of early clinical ECF disease were fever and enlarged parotid or prescapular lymph nodes. Clinical cases were categorized as mild, 24% (18) or moderate, 76% (56). There was an overall recovery rate of 100% (74) of the ECF cases whereby 94.6% (70) recovered promptly and 5.4% (4) recovered slowly. Based on blood analysis, prevalence of ECF at baseline was 3.7% (9) by microscopy, 31.1% (76) by PCR and 38.1% (93) by ELISA. A significant increase (p < 0.05) was shown by the increased number of calves with T. parva specific antibodies in the sera from 38.1% at baseline to 68.8% after six months. High antibody levels (positive percentage ≥ 50%) were detected in all ECF-treated and recovered calves at the end of six months. The acquired immunity to ECF was high in treated and recovered cattle, indicating that natural exposure to infection, accurate early diagnosis and effective treatment enhance development of immune-protection in indigenous cattle in an endemic area. The prominent early clinical symptoms for ECF could be exploited in the development of decision support tools for chemotherapy and other integrated control measures.
Keywords: Theileria parva; early diagnosis; treatment